Genetic diversity, distribution, and evolution of chicken anemia virus: A comparative genomic and phylogenetic analysis - Shah, Pir Tariq; Bahoussi, Amina Nawal; Cui, Xiaogang; Shabir, Shaista; Wu, Changxin; Xing, Li (Frontiers in Microbiology, 2023)
Chicken infectious anemia (CIA) is an immunosuppressive poultry disease that causes aplastic anemia, immunosuppression, growth retardation and lymphoid tissue atrophy in young chickens and is responsible for huge economic losses to the poultry industry worldwide. The disease is caused by the chicken anemia virus (CAV), which belongs to the genus Gyrovirus, family Anelloviridae. Herein, we analyzed the full-length genomes of 243 available CAV strains isolated during 1991-2020 and classified them into two major clades, GI and GII, divided into three and four sub-clades, GI a-c and GII a-d, respectively. Moreover, the phylogeographic analysis revealed that the CAVs spread from Japan to China, China to Egypt and subsequently to other countries, following multiple mutational steps. In addition, we identified eleven recombination events within the coding and non-coding regions of CAV genomes, where the strains isolated in China were the most active and involved in ten of these events. Furthermore, the amino acids variability analysis indicated that the variability coefficient exceeded the estimation limit of 1.00 in VP1, VP2 and VP3 proteins coding regions, demonstrating substantial amino acid drift with the rise of new strains. The current study offers robust insights into the phylogenetic, phylogeographic and genetic diversity characteristics of CAV genomes that may provide valuable data to map the evolutionary history and facilitate preventive measures of CAVs.